An interpretative phenomenological analysis: How educational planning can resolve the teacher marginalization? - Hartini, Nani; Widaningsih; Garnasih, Wulan (Indonesian Research Journal in Education |IRJE|, 2025)
This research explores the experiences of marginalization among teachers in Indonesia, focusing on the exclusion from decision-making, lack of professional recognition, and limited growth opportunities. Using qualitative interviews with 18 teachers, data were collected through in-depth interviews and analyzed thematically with Interpretative Phenomenological Analysis (IPA) method. The findings reveal that teachers face systematic exclusion in policy formulation and decision-making processes, a lack of recognition for their contributions, and restricted opportunities for professional development. The research highlights the role of educational planning as a potential solution to mitigate these issues by fostering a more inclusive, collaborative, and responsive educational system. The research advocates for a paradigm shift in educational planning to address the systemic inequities that contribute to the marginalization of teachers, emphasizing the importance of involving educators in decision-making processes and professional development programs.